(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to find out how the implementation of the Population Administration Information System (SIAK) policy in the Population and Civil Registration Office of North Bolaang Mongondow Regency.The study uses a descriptive-qualitative approach. The focus of research is the four dimensions of public policy implementation, namely communication, resources, disposition, and bureaucratic structure. The research informants were the head of the department, the heads of fields, staff / implementing staff, and the community served. Data collection uses interview guidelines, while the analysis technique used is the analysis of interactive models from Miles and Hubernann.Based on the results of the study concluded: (1) Communication is carried out well and effectively. SIAK’s policies are disseminated to the public both directly and through the assistance of sub-district governments and village governments, through information boards in the Office, and through brochures or leaflets, electronic media such as websites, internet sites. (2) Human resources for the implementation of SIAK policies are inadequate in quantity; but the quality is good enough. Financial resources for the implementation of SIAK are sufficient to be seen from the funds / operational costs allocated; but work facilities and infrastructure are still inadequate for the implementation of SIAK in prime. (3) Disposition (employee attitude) in implementing SIAK policies is quite good seen from commitment, consistency, honesty, and democratic attitude in carrying out services with the SIAK system. (4) The bureaucratic structure in implementing the SIAK policy has been well organized and effective. SOP (Standard Operating Procedure) and organizational structure and division of labor. Keywords: policies, population administration information systems